Countering Financial Terrorism ("Journal "U". Economy. Management. Finance.", 2021)
Financial terrorism is understood as a certain way of dominating the owners of big capital, where the basis is the exploitation of the lower class by the upper class in order to ensure the satisfaction of their needs, as well as to further increase welfare. This article discusses the key tools that provide countering financial terrorism.
Keywords: terrorism; financial terrorism